Truth or die - Hoh, Diane; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1994)
As Salem University freshman Parrie Moore becomes involved in what at first appears to be a harmless game of Truth or Dare, the dares gradually becomes stranger and more dangerous, and the game takes on a life of its own.
Keywords: Nightmare Hall (Imaginary organization) -- Fiction; Women college students -- Fiction; Games -- Fiction; Horror fiction; Young adult fiction